Delay in seeking health care from community residents during a time with low prevalence of COVID-19: A cross-sectional national survey in China - Wang, Ziyu; Tang, Yurong; Cui, Yu; Guan, Hanwen; Cui, Xiaoqian; Liu, Yuan; Liu, Yanni; Kang, Zheng; Wu, Qunhong; Hao, Yanhua; Liu, Chaojie (Frontiers in Public Health, 2023)
BACKGOUND: The pandemic of COVID-19 has significant implications on health resources allocation and health care delivery. Patients with non-COVID illness may have to change their care seeking behaviors to mitigate the risk of infections. The research aimed to investigate potential delay of community residents in seeking health care at a time with an overall low prevalence of COVID-19 in China. METHODS: An online survey was conducted in March 2021 on a random sample drawn from the registered survey participants of the survey platform Wenjuanxing. The respondents who reported a need for health care over the past month (n=1317) were asked to report their health care experiences and concerns. Logistic regression models were established to identify predictors of the delay in seeking health care. The selection of independent variables was guided by the Andersen’s service utilization model. All data analyses were performed using SPSS 23.0. A two-sided p value of <0.05 was considered as statistically significant. KEY RESULTS: About 31.4% of respondents reported delay in seeking health care, with fear of infection (53.5%) as a top reason. Middle (31-59 years) age (AOR=1.535; 95% CI, 1.132 to 2.246), lower levels of perceived controllability of COVID-19 (AOR=1.591; 95% CI 1.187 to 2.131), living with chronic conditions (AOR=2.008; 95% CI 1.544 to 2.611), access to Internet-based medical care (AOR=2.529; 95% CI 1.960 to 3.265), and higher risk level of the region (AOR=1.736; 95% CI 1.307 to 2.334) were significant predictors of the delay in seeking health care after adjustment for variations of other variables. Medical consultations (38.7%), emergency treatment (18.2%), and obtainment of medicines (16.5%) were the top three types of delayed care. CONCLUSIONS: Delay in seeking health care remained at a relatively high level when the number of new COVID-19 cases was low, which may present a serious health risk to the patients, in particular those living with chronic conditions who need continuous medical care. Fear of infection is the top reason for the delay. The delay is also associated with access to Internet-based medical care, living in a high risk region, and perceived low controllability of COVID-19.